Evaluasi pelaksanaan program kesehatan usia lanjut di puskesmas se-Kabupaten Sleman = Evaluation of implementation for health program of aged in all community health centers in Sleman district - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Background: The health program of aged in Yogyakarta Province was implemented only in Sleman District which has a gave complete report to Office of Health in province. Therefore the aim of research is to assess the implementation of the health program of aged in community health center (CHC) in Sleman District. Method: This is a descriptive-explorative study that used qualitative data as the method. Data was collected from: 1) Focus group discussion to program coordinators, public figure, and aged